European Union : Publication of Financial Sector Assessment Program Documentation-Detailed Assessment of Observance of the CPSS-IOSCO Principles for Financial Market Infrastructures. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
This paper discusses the main findings of the Detailed Assessment of Observance of the Committee on Payment and Settlement Systems-International Organization of Securities Principles for Financial Market Infrastructures (FMIs) for the European Union. Euroclear Bank's risk framework is generally sound. Euroclear Bank should become operationally ready to fully implement plans for recovery and the orderly winding-down of operations. In anticipation of the emerging international regulatory standards and frameworks on recovery and resolution of FMIs, Euroclear Bank has developed recovery plans and plans for the orderly winding down of its operations. Important risk measures have been taken to reduce credit risk, but further improvements are needed to comply with the international standards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet